Impact Assessment of Organizational Stress in Agriculture Sector (International Journal of Agriculture and Sustainable Development, 2021)
Govt officials of the agriculture department are key persons in pointing out the drawback which causes a decline in overall performance. To do so, a questionnaire was prepared and circulated among officials of the agriculture department. By identifying potential occupational stressors, this exploratory study hopes to close the gap. The researchers also want to examine if the level of role stress that agricultural workers experience is influenced by their employment status (permanent or temporary). Stress has been investigated in connection to concerning variables e.g., gender, age, and marital status. The data was collected in Sep 2020 from 50 temporary and 35 permanent officials. Research shows that temporary officers are more stressed than their permanent counterparts. More than half of the extension workers reported feeling overwhelmed by resource inadequacy. It was observed that stress level increase with age. The married officials were also observed more stressed which may be due to domestic reasons however their temporary status affected their efficiency badly. In the future, researchers should investigate the prevalence of stress in public extension officials and its impact on employee well-being, job satisfaction, and job performance, as well as test and implement the evaluation mechanisms.